The Economic Value of Shark and Ray Tourism in Indonesia and Its Role in Delivering Conservation Outcomes - Mustika, Putu Liza Kusuma; Ichsan, Muhammad; Booth, Hollie (Frontiers in Marine Science, 2020)
As a hotspot of species diversity and fishing pressure, Indonesia is a global priority for the conservation of sharks, rays and their cartilaginous relatives (herein ‘sharks’). The high value marine tourism industry in Indonesia can create economic incentives for protecting and sustainably managing marine ecosystems and species, including sharks. This study estimates the economic value of shark and ray tourism in Indonesia and explores tourist preferences and local community perceptions of the tourism industry to understand the current and potential future role of this industry in shark and ray conservation. We identified 24 shark tourism hotspots across 14 provinces, with primary data collected from 365 tourists and 84 local community members over six case study sites. We use Purchasing Power Parity and travel efforts to extrapolate expenditures to other tourism sites. We estimate that at least 188,931 dedicated or partially dedicated shark tourists visit Indonesia each year. The median annual expenditures of these shark tourists is estimated at USD 22 million (for 2017), accounting for at least 7% of the total USD 1 billion marine tourism revenue in Indonesia in 2017 and 1.45x the value of annual shark exports in the country (inflation-adjusted to 2017 values). If sharks were absent from the surveyed sites, Indonesia’s tourism industry could lose ~ 25% of these dive tourist expenditures. Despite this considerable value, our study indicates a mismatch between the absolute economic value of shark and ray tourism and its role in providing an incentive for conservation. Results from interviews with local communities in or near shark and ray tourism sites indicate that shark fishers are not well placed to receive direct economic benefits from shark and ray tourism. Since overfishing is the primary threat to shark populations, failure to engage with and appropriately incentivise these stakeholders will be detrimental to the success of Indonesia’s shark conservation efforts. If shark populations continue to decline due to insufficient conservation actions, the tourism industry could suffer economic losses from shark and ray tourism of more than USD 121 million per annum by 2027, as well as detrimental impacts on species, marine ecosystems, fisheries and people.